A Low Quiescent Current Fast Settling Capacitor-less Low Drop Out Regulator Employing Multiple Loops - Suresh Alapati; Patri Sreehari Rao (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents a fast transient and low noise capacitor-less LDO using multiple loops. The proposed LDO exploits adaptive biasing, bulk modulation and a fast reacting control loop for achieving high performance striking reasonable tradeoffs among quiescent current, transient response and stability. The proposed LDO offers a load regulation of 0.095µV/mA while consuming quiescent current of 16 µA. It exhibits a load transient of 134.23mV with a settling time of 240.8ns against 0 to 100mA load variation with 40pF output capacitor. It exhibits an integrated noise of 31.027 pV2 /Hz at 10 Hz for a maximum load current of 100mA. The proposed LDO is designed using 0.18-µm 1P6 CMOS process.